Plasmonically Enhanced Schottky Photovoltaic Devices - M. Farhat (14415657) (2017)
Solar-cells based on Schottky junctions between metals and semiconductors (without or with an intermediate insulator) are among the main possibilities towards economical photovoltaic conversion of the solar energy. This is mainly due to their structural simplicity and hence the ease of their realization. We propose here a new kind of light-harvesting devices using plasmonic nano-antenna gratings, that enhance the absorption of light over a broadband spectrum, and permit the reduction of thickness of the cell dramatically, with efficiency around 15% for 3 micrometers ultra-thin Silicon cell. We show that this technique may provide a new avenue in low cost fabrication of thin-film solar-cells. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-017-14528-0